Net energy yield and carbon footprint of summer corn under different N fertilizer rates in the North China Plain - Zhan-biao WANG; Xin-ya WEN; Hai-lin ZHANG; Xiao-hong LU; Fu CHEN (Journal of Integrative Agriculture)
Excessive use of N fertilizer in intensive agriculture can increase crop yield and at the same time cause high carbon (C) emissions. This study was conducted to determine optimized N fertilizer application for high grain yield and lower C emissions in summer corn (Zea mays L.). A field experiment, including 0 (N0), 75 (N75), 150 (N150), 225 (N225), and 300 (N300) kg N ha−1 treatments, was carried out during 2010–2012 in the North China Plain (NCP). The results showed that grain yield, input energy, greenhouse gas (GHG) emissions, and carbon footprint (CF) were all increased with the increase of N rate, except net energy yield (NEY). The treatment of N225 had the highest grain yield (10 364.7 kg ha−1) and NEY (6.8%), but the CF (0.25) was lower than that of N300, which indicates that a rate of 225 kg N ha−1 can be optimal for summer corn in NCP. Comparing GHG emision compontents, N fertilizer (0–51.1%) was the highest and followed by electricity for irrigation (19.73–49.35%). We conclude that optimazing N fertilizer application rate and reducing electricity for irrigation are the two key measures to increase crop yield, improve energy efficiency and decrease GHG emissions in corn production.